Full N, N-Methylation of 4, 4′-Methylenedianiline with Dimethyl Carbonate: A Feasible Access to 4, 4′-Methylene bis(N, N-Dimethylaniline). (18th April 2018) - Qiu, Zegang; Wang, Kunjie; Li, Zhiqin; Li, Tao; Bai, Jinhao; Yin, Chanjuan; Ye, Xiushen; Liu, Haining
Abstract : The full N, N-methylation of 4, 4′-methylenedianiline (MDA) with dimethyl carbonate (DMC) was investigated. The yield of the major product 4, 4′-methylene bis(N, N-dimethylaniline) (MBDMA) reached as high as 97% over NaY catalyst at 190°C for 6 h. The catalyst could be used for two more times with acceptable MBDMA yields higher than 90%. The main by-products were identified as three N-methylated derivatives. Surprisingly, the formation of the N-methoxycarbonylation product was extremely restrained, which could be produced in high yields of 98% on zinc acetate catalyst. Furthermore, the reaction pathway to the major product MBDMA was proposed. Finally, a feasible synthetic route of 4, 4′-methylene bis(N, N-dimethylaniline) (MBDMA) was established, featuring a high yield, mild reaction conditions, and simple operations.